Epistatic interactions of major effect drought QTLs with genetic background loci determine grain yield of rice under drought stress - Yadav, Shailesh; Sandhu, Nitika; Majumder, Ratna Rani; Dixit, Shalabh; Kumar, Santosh; Singh, S.P.; Mandal, N.P.; Das, S.P.; Yadaw, Ram Baran; Singh, Vikas Kumar; Sinha, Pallavi; Varshney, Rajeev K.; et al. (Springer, 2019)
Epistatic interactions of QTLs with the genetic background and QTL-QTL interaction plays an important role in the phenotypic performance of introgression lines developed through genomic-assisted breeding (GAB). In this context, NIL pairs developed with various drought QTL (qDTY) combinations in the genetic background of IR64, TDK1-Sub1and Savitri backgrounds were utilized to study the interactions. Multi-season phenotyping of NIL pairs harboring similarqDTYcombinations provided contrasting performance for grain yield under drought (RS) (classified as high and low yielding NILs) but nearly similar performance under non-stress(NS) conditions. Genome wide genotyping data revealed a total of 16, 5 and 6 digenic interactions were detected under RS conditions in low yielding NILs of IR64, TDK1-Sub1and Savitri respectively while no significant interaction was found in high yielding NILs under RS and NS conditions in any of the genetic backgrounds used in this study. It is evident from this study that existence of epistatic interactions between QTLs with genetic background, QTL-QTL interaction and interactions among background markers loci itself on different chromosomes influences the expression of a complex trait such as grain yield under drought. The generated information will be useful in all the GAB program of across the crops for precise breeding.